Correlation Between Hemoglobin Levels, Hematocrit With Serum Erythropoietin In Erythrocytosis Patients - Santoso, Didik Agus; Fuadi, Muhamad Robi’ul (British Journal of Healthcare and Medical Research, 2023)
Background: Erythrocytosis is a condition where hemoglobin and hematocrit levels increase, in men (>16.5 g/dL; >49%) and women (>16.0 g/dL; >48%). Erythrocytosis results from an absolute increase in erythrocyte mass (absolute erythrocytosis/polycythemia), either primary or secondary, and as a result of a decrease in plasma volume (relative erythrocytosis). The prevalence of primary erythrocytosis in America is approximately 44 per 100,000 people. The incidence is most common in men, young adults to old age. The prevalence of secondary erythrocytosis is difficult to estimate and is much higher but data are limited and the causes are diverse. The condition of erythrocytosis is at risk of vascular complications and thrombosis. The diagnosis of polycythemia in erythrocytosis patients requires a confirmatory examination of the JAK2 V617F mutation which is expensive and laboratories rarely carry it out, so an alternative erythropoietin examination is needed to differentiate primary or secondary erythrocytosis. Objective: This study aims to analyze the correlation between hemoglobin levels, hematocrit and serum erythropoietin in erythrocytosis patients. Methode: This research is an observational study-cross sectional, with measurements of serum hemoglobin, hematocrit and erythropoietin levels in erythrocytosis patients taken by simple random sampling, in Dr Darsono Hospital, Pacitan Regency. Statistical analysis used the SPSS program with the Pearson correlation test. Result: The number of samples was: 56 samples, with characteristics: 89% men and an average age of 46 years. Average hemoglobin level: 17.3 mg/dL, hematocrit: 50.3% and average erythropoietin: 0.67 mIU/mL (reference value: 2.9-5.0 mIU/mL), lowest level 0.01 mIU/mL and highest 4.62 mIU/mL. The results of the correlation analysis found that there was an insignificant correlation between hemoglobin levels and serum erythropoietin (r= 0.165 and p= 0.256). There was a non-significant correlation between hematocrit and serum erythropoietin (r= 0.115 and p= 0.431). Discussion: There were low mean erythropoietin levels in the erythrocytosis patients in this study. There was an insignificant correlation between hemoglobin levels, hematocrit and serum erythropoietin in erythrocytosis patients. Conclusion: Serum erythropoietin examination is needed to screen for primary and secondary causes of erythrocytosis, before carrying out further examination with the JAK2 V617F mutation as confirmation of primary erythrocytosis (polycythemia vera).